The effect of education on knowledge and attitude In halal and tayyib food selection among Muslim - Zakia Umami; Amalina Ratih Puspa; Muhammad Asrul Irawan (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2023)
ABSTRAKLatar Belakang: Jumlah penduduk muslim sebanyak 236.53 juta pada tahun 2021, atau sebesar 86,9% dari total populasi penduduk Indonesia yang berjumlah 273,32 juta. Di Indonesia, Pemerintah mewajibkan agar semua produk pangan disertifikasi halal, akan tetapi belum semua produsen pangan mengerti kepentingan dari sertifikasi halal.Tujuan: Tujuan dari penelitian ini adalah untuk menganalisis pengetahuan dan sikap dalam pemilihan pangan halal dan thoyyib pada umat muslim. Metode: Penelitian ini menggunakan desain eksperimental dengan jumlah responden sebesar 89 orang. Teknik sampling yang digunakan adalah accidental sampling. Pemberian edukasi terkait pangan halal dan thoyyib diberikan secara online melalui zoom meeting. Sebelum dan sesudah edukasi dilakukan pengukuran pengetahuan dan sikap menggunakan kuesioner online melalui google form. Hasil: Responden yang mendapatkan informasi mengenai pangan halal dan thoyyib dari media social sebesar 88,76%. Terdapat perbedaan yang signifkan antara pengetahuan dan sikap sebelum dan setelah pemberian edukasi (p<0.005). Nilai rata-rat pengetahuan meningkat setelah edukasi, namun tidak pada sikap yang menurun setelah edukasi.Kesimpulan: Pemberian edukasi dapat meningkatkan pengetahuan terkait pangan halal dan thoyyib (p<0,005). Pada penelitian selanjutnya edukasi dapat diberikan baik secara daring maupun luring dengan media edukasi yang lebih menarik.  KATA KUNCI: edukasi; halal; online; pangan; thoyyib ABSTRACT Background: Total Muslim population in Indonesia is 237.53 million in 2021, this number is equivalent to 86.9% of the country's population of 273.32 million people. In Indonesia, the government requires all products to be halal-certified, but still, not all producers understand the importance of halal certification. They are constrained by costs and lengthy procedures in obtaining halal certification. Objectives: The objective of this study was to analyze knowledge and attitudes in the selection of halal and tayyib food among Muslim. Methods: This was experimental research using an accidental sampling method. The samples were 89 samples. Inclusion criteria are Muslim adolescents and adults who are willing to be sampled. The research steps were: 1) compiling educating materials composed of “The Advantage of Consuming Halal and Tayyib Food for Health” and “Halal: from A to Z and Critical Points of Modern Food”, 2) developing educational-purpose Powerpoint media, 3) giving a pretest to identify respondent knowledge and attitude before education, 4) giving education and carrying out a discussion online via Zoom Meeting for three hours, and 5) giving a posttest to identify respondent knowledge and attitudes after education.Results: Samples who get information related to halal food mostly obtained from social media by 88.76%. There was a significant difference in knowledge and attitudes regarding the selection of halal and tayyib food after being given education (p<0.005). The average knowledge score increased after education, but the average attitude score decreased after education.Conclusions: Education on halal and tayyib food, as attested to this research, could elevate knowledge yet not change attitudes. Before and after education knowledge was significantly different (p <0.005). Future researchers are expected to give online or offline education for a longer duration and use more attractive media.KEYWORDS: education; food; halal; online; tayyib